Du problème frontalier au projet transfrontalier : vers une gouvernance territoriale ? - Corentin Dayez; Fabienne Leloup; Solange Verger (Territoire en Mouvement)
The recent research on local government policy making and territorial development leads to analyze differently cross-border activities. These activities may be inherently connected to each other and shape a global and territorial scheme ; they create new local relations, new rules, new processes in order to develop the specific cross-border region. Based on a theoretical review and three specific situations, the paper points out the role of local coordination, “fittings”, identity anchorage - or innovation – in these “new winning cross-border areas”.